Does HbA1c Level Have Clinical Implications in Diabetic Patients Undergoing Coronary Artery Bypass Grafting? A Systematic Review and Meta-Analysis - Jia Zheng; Jing Cheng; Tong Wang; Qian Zhang; Xinhua Xiao (International Journal of Endocrinology)
Aims/Introduction. The aim of the present study was to investigate whether HbA1c was related to clinical outcomes in diabetic patients undergoing CABG surgery. Materials and Methods. A literature search was carried out satisfying the predefined inclusion criteria from Pubmed, Embase, and Cochrane Library. Differences were expressed as odds ratios (ORs) with 95% confidence intervals (CIs) to assess the relationships of preoperative HbA1c levels and clinical prognosis in diabetic patients. Results. 7895 diabetic patients undergoing CABG surgery from eight published studies were finally involved in this meta-analysis. Combined analyses revealed that the higher HbA1c level was significantly associated with increased risks of all-cause mortality (OR 1.56, 95%CI 1.29–1.88), myocardial infarction (OR 2.37, 95%CI 1.21–4.64), and stroke (OR 2.07, 95%CI 1.29–3.32) after CABG surgery. However, there was no significant relationship between HbA1c levels and renal failure (OR 2.08, 95%CI 0.96–4.54) in diabetic patients undergoing CABG surgery. Conclusions. Our meta-analysis demonstrated that the HbA1c level is potentially associated with increased risks of all-cause mortality, myocardial infarction, and stroke in diabetic subjects undergoing CABG surgery. However, further clinical studies with larger sample sizes and longer follow-up period are urgently warranted.